A place called home: Encounters with libraries. Issue 1 (April 2018) - Hudson, John
Libraries exist the world over across diverse cultures and have been in existence since the dawn of civilisation. Libraries can be seen as a collection of marks, often representing sounds, made upon some kind of support, such as stone, papyrus, paper or magnetic discs, which require deciphering and interpretation to have significance. Whether tiny island libraries or huge national libraries, each offers resources that help define identity at a global, national, community and personal level. The library has many roles to play, one that cannot be measured by statistics alone; it embodies freedom of speech and the principles of democracy but can and has been a means of social control; it is often a spontaneous expression of community and conviviality, sharing viewpoints and knowledge or it can be an engineered, assertive national statement; it is often a mixture of all these. The library is more than the sum of its parts and is an expression of the relationship between the human and the mysterious universe we live in.